2013
DOI: 10.1097/meg.0b013e32836171c4
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous α1-antitrypsin Z allele mutation in presumed healthy donor livers used for transplantation

Abstract: Presumed healthy donor organs containing the Z allele were used for transplantation in 0.8% of cases in our series. As the presence of a Z allele is an independent risk factor of aggravation of chronic liver disease, AATZ accumulation in biopsies after liver transplantation should be actively looked for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…There is evidence that the presence of the Z allele even in the heterozygous state increases the risk of chronic liver disease and interacts with hepatotoxins to increase the risk of cirrhosis that presents in late adulthood and increases the risk of decompensation . A review of cadaveric transplant liver biopsies from Europe identified the mutated α 1 AT Z protein in 0.8% of donors and was an independent risk factor for later chronic liver disease in the graft …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the presence of the Z allele even in the heterozygous state increases the risk of chronic liver disease and interacts with hepatotoxins to increase the risk of cirrhosis that presents in late adulthood and increases the risk of decompensation . A review of cadaveric transplant liver biopsies from Europe identified the mutated α 1 AT Z protein in 0.8% of donors and was an independent risk factor for later chronic liver disease in the graft …”
Section: Discussionmentioning
confidence: 99%
“…Human pluripotent stem cells (hPSCs), including both embryonic (hESCs) and induced pluripotent stem cells (hiPSCs), represent an unlimited source of differentiated cell types and tissues for modeling human development and disease in vitro, for developing new cell-based therapeutics and for establishing new drug discovery and predictive toxicology platforms (Cherry and Daley, 2012;Diecke et al, 2014;Fox et al, 2014;Holmgren et al, 2014;Leung et al, 2013;Medine et al, 2013;Roelandt et al, 2013;Sjogren et al, 2014;Szkolnicka et al, 2014;Trounson et al, 2012;Zhou et al, 2014). Translating this potential of stem cells into practice is, however, dependent on the availability of directed differentiation strategies that enable the efficient, reproducible and cost-effective generation of the lineage of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are virtually no data regarding the safety of using heterozygous A1AT donors in LT. Roelandt et al found that 0.8% of presumed healthy transplanted livers in their study group were heterozygous for A1AT . A few cases of LDLT have been performed, but no details are available regarding specific outcomes or longterm follow‐up .…”
Section: Alpha‐1‐antitrypsin Deficiencymentioning
confidence: 91%
“…No available data A1AT deficiency Insufficient evidence (35,36,79) No available data Insufficient evidence (37)(38)(39)(80)(81)(82)(83)(84)…”
Section: G6pd Deficiencymentioning
confidence: 99%